Barbados : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2016)
This Selected Issues paper discusses data issues and postcrisis growth in Barbados. An analysis of the data on Barbados shows very clear inconsistencies among the various measures of economic development. Although real growth seems to have evolved broadly in line with the rest of the Caribbean, nominal growth and inflation developments suggest that Barbados was hit much harder by the global financial crisis. At the same time, these data may also be misleading. Nominal GDP seems to have inadequate coverage, and inflation is much higher in Barbados than in similar economies in the region.